Cardiac biomarkers and left ventricular systolic function in acute myocardial infarction with ST- segment elevation in diabetes mellitus type 2 patients - Mirela Halilčević; Edin Begić; Alen Džubur; Nirvana Šabanović-Bajramović; Mevludin Mekić; Malik Ejubović; Amela Džubur; Ena Štimjanin (Medicinski glasnik, 2020)
Aim: To determine a status of systolic function in patients with diabetes mellitus (DM) type 2 with ST-segment elevation acute myocardial infarction (STEMI), to determine values of cardiac biomarkers in patients with DM type 2 with STEMI and correlate the parameters with ejection fraction of left ventricle (EFLV). Methods: A total of 80 patients were divided into two groups, the study group (group I) consisting of 40 patients admitted with the diagnosis of DM type 2 and STEMI, and a control group (group II) with 40 patients with STEMI without diagnosed DM type 2. Cardiac biomarkers-creatine kinase MB fraction (CKMB), and troponin I were monitored. The EFLV was evaluated echocardiographically (using Simpson method) five days after primary percutaneous coronary intervention (pPCI). Results: In the group I the EFLV five days after pPCI was significantly correlated with troponin values (with a minimum r =-0.47; p=0.002, a maximum r =-0.339; p = 0.032, as well as with an average value of r =-0.389; p=0.013), and with an average CK value (r =-0.319; p=0.045). In the group II there was a significant negative correlation of EFLV with the maximum value of troponin (r =-0.309; p=0.05). Conclusion: Troponin values have an effect on the EFLV after STEMI, and thus on the left ventricular status, as well as on the pharmacological modality itself.
Keywords: prognosis; ST elevation myocardial infarction; troponin